2017
DOI: 10.3389/fpls.2017.02166
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Affecting Quality and Health Promoting Compounds during Growth and Postharvest Life of Sweet Cherry (Prunus avium L.)

Abstract: Sweet cherries are attractive fruits due to their taste, color, nutritional value, and beneficial health effects. Sweet cherry is a highly perishable fruit and all quality attributes and the level of health promoting compounds are affected by growth conditions, picking, packing, transport, and storage. During production, the correct combination of scion × rootstock will produce fruits with higher firmness, weight, sugars, vitamins, and phenolic compounds that boost the fruit antioxidant activity. Orchard manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
64
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 176 publications
(230 reference statements)
5
64
0
2
Order By: Relevance
“…reported better maintenance of phenol levels in cornelian cherry fruits with MAP treatments. Correia et al . indicated that MAP could be used as a significant tool to increase health‐promoting compounds and shelf life of sweet cherry fruits.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…reported better maintenance of phenol levels in cornelian cherry fruits with MAP treatments. Correia et al . indicated that MAP could be used as a significant tool to increase health‐promoting compounds and shelf life of sweet cherry fruits.…”
Section: Resultsmentioning
confidence: 99%
“…29 The anthocyanin accumulation in skin may have great contributions to appearance, taste, flavor, aroma, texture, nutritional composition, and antioxidant activity of the fruits. 29,37,41 Fully ripe fruits with a red peel color generally have greater anthocyanin, which is a red color pigment. Thus, Gunduz et al 35 reported greater anthocyanin contents for fully ripe cornelian cherry fruits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this study, 2 or 4 g · L -1 GB in hydro-cooling water applied postharvest did not affect fruit skin color, SSC, or TA of 'Lapins' or 'Regina' cherries, but these treatments markedly reduced FF during storage at 0°C compared with control (Table 1). High FF is strongly preferred for sweet cherry so they are better able to withstand the handling, sorting, packing, storing, and transporting processes (Correia et al, 2017). Loss of FF directly impacts weight loss, off flavors, flesh browning, surface pitting, discoloration of the green stem, and fungal rotting (Kappel et al, 1996;Turner et al, 2005;Zheng et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Preharvest and postharvest applications of plant growth regulators have been proven to slow the deterioration of cherry quality (Correia et al, 2017;Valero et al, 2011;Zhang and Whiting, 2013). Glycine betaine (GB; N, N, N-trimethylglycine), which is a natural osmoregulator derived from sugar beet molasses, has a crucial role in preventing fruit from chilling injury, oxidative stress, and pathogen growth (Liu et al, 2011;Ragab et al, 2015;Razavi et al, 2018;Shan et al, 2015Shan et al, , 2016.…”
mentioning
confidence: 99%